PRECISE ANALYSIS OF 234U/238U RATIO USING UO2+ ION WITH THERMAL IONIZATION MASS SPECTROMETRY FOR NATURAL SAMPLES - Yokoyama T.; Makishima A.; Nakamura E. (My University, 2001)
We have developed a new, highly precise method for U isotopic analysis using a thermal ionization mass spectrometry (TIMS) by measuring UO2+ ions emitted from a very small amount (100-10 ng) of U. A new ionization activator, a silicic acid-diluted phosphoric acid solution, was found to be effective not only for producing a strong and stable UO2+ ion beam, but also for keeping the mass fractionation during measurement small and constant. U isotope analysis was carried out by a ''dynamic multi collection'' method using three Faraday cup collectors and a secondary electron multiplier in ion counting mode with RPQ (RPQ-SEM). For precise isotope analysis, baselines of the Faraday cups and a conversion factor between Faraday cups and the RPQ-SEM were precisely determined simultaneously with U isotope collection. Analytical precision and reproducibility of 234U/238U ratio ranged from 0.10% to 0.38% (2σmean) and from 0.13% to 0.31% (2σ), respectively, for 100-10 ng of U extracted from a natural rhyolitic obsidian. The precision and reproducibility were improved compared with previous studies, and thus, our method is especially useful for samples with very low abundance of U.
Keywords: PRECISE ANALYSIS; 234U/238U RATIO; THERMAL IONIZATION MASS SPECTROMETRY